2015
DOI: 10.1007/s11552-015-9765-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Subluxation on the Severity of Symptoms, Disability, and the Results of Operative Treatment in TMC Osteoarthritis with Total Joint Arthroplasty

Abstract: This study indicates that radial subluxation may not be an important factor in symptoms and function in patients with symptomatic TMC osteoarthritis without severe scaphotrapezio (ST) joint degeneration. In addition, preoperative subluxation seems not to be important for the result after total joint arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Newer studies revealed that the radiographic staging for severity of CMCJ I OA by Eaton-Littler (1973) and Eaton-Glickel (1987) alone are likely unable in decision making which treatment would be appropriate. Thus, it has been recommended to introduce a new classification that incorporates more the preoperative patient's disability; and diagnosis and treatment should be based on the surgeon's qualitative assessment combining history, physical examination, the patients claims in activities of daily living, radiographic evaluation, surgical experience of the treating physicians, and subjective patients factors [9,[39][40][41][42][43][44]. Moreover, psychological factors or disorders of the patients may have influence on the outcome after treatment of CMCJ I OA [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Newer studies revealed that the radiographic staging for severity of CMCJ I OA by Eaton-Littler (1973) and Eaton-Glickel (1987) alone are likely unable in decision making which treatment would be appropriate. Thus, it has been recommended to introduce a new classification that incorporates more the preoperative patient's disability; and diagnosis and treatment should be based on the surgeon's qualitative assessment combining history, physical examination, the patients claims in activities of daily living, radiographic evaluation, surgical experience of the treating physicians, and subjective patients factors [9,[39][40][41][42][43][44]. Moreover, psychological factors or disorders of the patients may have influence on the outcome after treatment of CMCJ I OA [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…A tip pinch of 1 kg will generate 12 kg joint compression; and for the power grip, the load may be as high as 120 kg [25]. Additionally, recent evidence suggests that cup surveillance does not depend on the preoperative radiographic staging using the classifications by Eaton-Littler (1973) or Eaton-Glickel (1987); thus, for assessment the outcome of total TCMJ replacement it has been recommended in 2015 by Larsen et al [26] to introduce a new classification that incorporates more the preoperative patient's disability. When using non-cemented screw cups, it is also recommended to insert it without threading of the trapez bone to improve the primary insertion-related stability that is an important prerequisite for its secondary bony anchorage [27,28].…”
mentioning
confidence: 99%
“…That can be based either on long duration of symptoms or occult painful osteoarthritis in DRUJ that does not always correlate with the radiographic findings which is well known from other joints such as the carpometacarpal joint of the thumb (i.e. rhizarthrosis) [40,75]. For those cases it is recommended to take a osteocartilage specimen for histological examination while performing the USO that can be helpful for evaluation of postoperative discomfort (Figures 4 and 5).…”
mentioning
confidence: 99%